Manufacturing method of easy adhesion film
Patent Information
- Application Number
- JP2023139104
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2025-03-13
AI Technical Summary
【0012】 エマルション粒子径の小さい水系ポリウレタンを含む易接着組成物を用いて易接着層を形成することにより、ヘイズが小さく透明性の高い易接着フィルムが得られる。易接着フィルムは、偏光子保護フィルムとして好適に使用できる。
Smart Images

Figure 2025033401000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an easily adhesive film having an easily adhesive layer on the surface of a transparent film substrate. [Background technology]
[0002] Liquid crystal display devices and organic electroluminescence display devices are widely used as various image display devices such as mobile devices, car navigation devices, PC monitors, and televisions. Due to the display principle of the liquid crystal display device, a polarizing plate is arranged on the viewing side surface of the liquid crystal cell. In a transmissive liquid crystal display device, polarizing plates are arranged on both sides of the liquid crystal cell. In an organic electroluminescence display device, a circular polarizing plate (typically a laminate of a polarizing plate and a quarter-wave plate) may be arranged on the viewing side surface to prevent external light from being reflected by the metal electrode (cathode) and being viewed as a mirror surface.
[0003] Polarizing plates generally have a transparent film (polarizer protective film) on one or both sides of a polarizer for the purpose of protecting the polarizer, etc. A widely used polarizer is one in which iodine is adsorbed onto a polyvinyl alcohol (PVA) film and the molecules are oriented by stretching or the like.
[0004] As a polarizer protective film to be attached to the surface of a polarizer, a cellulose-based film such as cellulose acetate is widely used because of its excellent adhesion to a PVA-based polarizer. As a polarizer protective film, films made of resin materials such as acrylic, polyester, polycarbonate, and cyclic polyolefin are also being used. Films made of these resin materials generally have lower adhesion to a polarizer than cellulose-based films.
[0005] In order to improve the adhesion between a polarizer and a polarizer protective film, it has been proposed to use an easy-adhesion film having an easy-adhesion layer on a transparent film substrate as a polarizer protective film. For example, Patent Document 1 discloses an easy-adhesion film having an easy-adhesion layer containing a polyurethane resin on the surface of a film substrate. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 5354733 Summary of the Invention [Problem to be solved by the invention]
[0007] As image display devices become more highly precise, there is a demand for higher brightness and clearer image quality, and optical films such as polarizing plates are required to have lower haze and higher transmittance. An easy-adhesion film having a polyurethane-based easy-adhesion layer on a transparent film substrate has excellent adhesion to a polarizer, but the formation of the easy-adhesion layer tends to increase haze, which can cause a decrease in the single transmittance of the polarizing plate and a decrease in the clarity of a displayed image due to light scattering.
[0008] In view of the above, an object of the present invention is to provide an easily adhesive film that has excellent adhesion to a polarizer and high transparency. [Means for solving the problem]
[0009] The present invention relates to a method for producing an easy-adhesion film having an easy-adhesion layer on the surface of a transparent film substrate. An easy-adhesion composition is applied to a transparent film substrate, and the easy-adhesion composition is heated to remove the solvent, thereby forming an easy-adhesion layer. When removing the solvent from the easy-adhesion composition, the transparent film substrate coated with the easy-adhesion composition may be stretched in at least one direction while being heated.
[0010] The easy-adhesion composition is an aqueous solution containing a water-based polyurethane having an emulsion particle size of 20 nm or less. The water-based polyurethane is preferably one that does not have a crosslinked structure. The easy-adhesion composition may contain a crosslinking agent that can crosslink with the water-based polyurethane. The easy-adhesion composition may further contain fine particles.
[0011] The transparent film substrate may be an acrylic film. The thickness of the easy-adhesion layer may be 110 nm or more and 280 nm or less. Effect of the Invention
[0012] By forming an easy-adhesion layer using an easy-adhesion composition containing a water-based polyurethane having a small emulsion particle size, an easy-adhesion film having low haze and high transparency can be obtained. The easy-adhesion film can be suitably used as a polarizer protective film. [Brief description of the drawings]
[0013] [Figure 1] FIG. 2 is a cross-sectional view showing an example of the configuration of an easily adhesive film. [Diagram 2] FIG. 2 is a cross-sectional view showing an example of the configuration of a polarizing plate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] 1 is a schematic cross-sectional view showing an example of the configuration of the easy-adhesion film of the present invention. The easy-adhesion film 1 has an easy-adhesion layer 15 on at least one surface of a film substrate 11. Easy-adhesion layers may be provided on both surfaces of the film substrate.
[0015] An example of a use form of the easy-adhesion film is a polarizer protective film. Fig. 2 is a cross-sectional view showing a configuration example of a polarizing plate including an easy-adhesion film 1 as a polarizer protective film. A polarizing plate 100 includes an easy-adhesion film 1 bonded to one surface of a polarizer 5 via an adhesive layer 6. In the polarizing plate 100 shown in Fig. 2, a transparent protective film 2 is bonded to the other surface of the polarizer 5 via an adhesive layer 7.
[0016] [Film base material] A transparent film is preferable as the film substrate 11. The total light transmittance of the transparent film substrate is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. Examples of the resin material constituting the film substrate 11 include acrylic resins, polyester resins, polycarbonate resins, polyolefin resins, cyclic polyolefin resins, polystyrene resins, polyamide resins, and polyimide resins. When the easy-adhesion film is used as an optically isotropic polarizer protective film, the resin material of the film substrate 11 is preferably an acrylic resin or a cyclic polyolefin resin, and more preferably an acrylic resin, since it has small birefringence.
[0017] Examples of cyclic polyolefin resins include polynorbornene. Commercially available cyclic polyolefin resins include Zeonoa and Zeonex manufactured by Zeon Corporation, Arton manufactured by JSR Corporation, Apel manufactured by Mitsui Chemicals, and Topas manufactured by TOPAS ADVANCED POLYMERS. The cyclic polyolefin film preferably contains 50% by weight or more of cyclic olefin resin.
[0018] Examples of acrylic resins include poly(meth)acrylic acid esters such as polymethyl methacrylate, methyl methacrylate-(meth)acrylic acid copolymers, methyl methacrylate-(meth)acrylic acid ester copolymers, methyl methacrylate-acrylic acid ester-(meth)acrylic acid copolymers, methyl (meth)acrylate-styrene copolymers (MS resins, etc.), and polymers having alicyclic hydrocarbon groups (for example, methyl methacrylate-cyclohexyl methacrylate copolymers, methyl methacrylate-norbornyl (meth)acrylate copolymers, etc.).
[0019] In this specification, "(meth)acrylic" means acrylic and / or methacrylic. Acrylic resins include those containing acrylic acid or a derivative thereof as a constituent monomer component, and those containing methacrylic acid or a derivative thereof as a constituent monomer component.
[0020] The acrylic resin may be an acrylic resin having a glutaric anhydride structure as described in JP-A-2006-283013, JP-A-2006-335902, JP-A-2006-274118, etc.; and / or an acrylic resin having a lactone ring structure as described in JP-A-2000-230016, JP-A-2001-151814, JP-A-2002-120326, JP-A-2002-254544, JP-A-2005-146084, etc. The acrylic resin having a glutaric anhydride structure and the acrylic resin having a lactone ring structure have high heat resistance, high transparency, and high mechanical strength, and are therefore suitable for producing a polarizing plate having a high degree of polarization and excellent durability.
[0021] When the film substrate 11 is an acrylic film, the content of the acrylic resin in the film substrate is preferably 50% by weight or more, more preferably 60 to 98% by weight, and even more preferably 70 to 97% by weight. The acrylic film may contain a thermoplastic resin other than the acrylic resin. For example, by blending another thermoplastic resin, the birefringence of the acrylic resin is cancelled, and an acrylic film having excellent optical isotropy can be obtained. Furthermore, a thermoplastic resin other than the acrylic resin may be blended for the purpose of improving the mechanical strength of the film.
[0022] Examples of thermoplastic resins other than acrylic resins include olefin polymers, halogenated vinyl polymers, polystyrene, copolymers of styrene and acrylic monomers, polyesters, polyamides, polyacetals, polycarbonates, polyphenylene oxides, polyphenylene sulfides, polyether ether ketones, polysulfones, polyether sulfones, polyoxybenzylenes, polyamide imides, and rubber polymers.
[0023] The film substrate 11 may contain additives such as antioxidants, stabilizers, reinforcing materials, UV absorbers, flame retardants, antistatic agents, colorants, bulking agents, plasticizers, lubricants, fillers, etc. The resin material and additives may be mixed to form a thermoplastic resin composition such as pellets before forming into a film.
[0024] The thickness of the film substrate 11 is about 5 to 200 μm. From the viewpoints of mechanical strength, transparency, handleability, and the like, the thickness of the film substrate 11 is preferably 10 to 100 μm, and more preferably 15 to 60 μm.
[0025] The glass transition temperature Tg of the film substrate 11 is preferably 100° C. or higher, and more preferably 110° C. or higher. When the film substrate 11 is an acrylic film, as described above, the Tg of the acrylic film can be increased and the heat resistance can be improved by using an acrylic resin having a glutaric anhydride structure or an acrylic resin having a lactone ring structure as the acrylic resin. There is no particular upper limit to the Tg of the film substrate 11, but from the viewpoint of formability, etc., it is preferably 170° C. or lower.
[0026] Examples of the manufacturing method of the film substrate 11 include a solution casting method, a melt extrusion method, a calendar method, and a compression molding method. The film substrate 11 may be either an unstretched film or a stretched film. When the film substrate 11 is an acrylic film, from the viewpoint of improving mechanical strength, the acrylic film is preferably a stretched film stretched in at least one direction, and a biaxially stretched film is particularly preferable. By blending another thermoplastic resin so as to cancel the birefringence of the acrylic resin, an acrylic film with small retardation and excellent optical isotropy can be obtained even when stretched.
[0027] [Easy adhesive composition] An easy-adhesion composition is applied to the surface of the film substrate 11, and the solvent is removed by heating to form an easy-adhesion layer 15. By providing the easy-adhesion layer 15, it is possible to improve adhesion to films such as polarizers and glass substrates. In the present invention, an easy-adhesion composition containing a water-based polyurethane having a predetermined emulsion particle size is used.
[0028] <Water-based polyurethane> The easy-adhesion composition contains an aqueous polyurethane as a binder resin. The aqueous polyurethane is obtained by emulsifying polyurethane. The polyurethane is typically a reaction product of a polyol and a polyisocyanate. As the polyol component, a polymer polyol such as polyacrylic polyol, polyester polyol, or polyether polyol is preferably used. As the polyisocyanate, any of aliphatic diisocyanates, alicyclic diisocyanates, and aromatic diisocyanates can be used, and from the viewpoint of transparency, etc., aliphatic diisocyanates or alicyclic diisocyanates are preferred.
[0029] The aqueous polyurethane contained in the easy-adhesion composition preferably has a carboxy group. When the polyurethane has a carboxy group, a crosslinked structure can be introduced, and the adhesion between the easy-adhesion film 1 and a polarizer or the like tends to be improved. The polyurethane having a carboxy group can be obtained, for example, by reacting a chain lengthener having a free carboxy group in addition to a polyol and a polyisocyanate. Examples of the chain lengthener having a free carboxy group include dihydroxycarboxylic acid and dihydroxysuccinic acid. Examples of the dihydroxycarboxylic acid include dialkylolalkanoic acid such as dimethylolalkanoic acid (e.g., dimethylolacetic acid, dimethylolbutanoic acid, dimethylolpropionic acid, dimethylolbutyric acid, and dimethylolpentanoic acid).
[0030] The number average molecular weight of the polyurethane is preferably 5,000 to 600,000, and more preferably 10,000 to 400,000. The acid value of the polyurethane is preferably 10 to 50, and more preferably 20 to 45.
[0031] Water-based polyurethane may be reactive or non-reactive. Non-reactive water-based polyurethane is an emulsion of polyurethane. Reactive water-based polyurethane is an emulsion in which the terminal isocyanate groups of the reaction product (preolimer) of polyol and polyisocyanate are protected with a blocking agent.
[0032] The emulsification method of polyurethane is not particularly limited. For emulsification of hydrophobic polyurethane, a method using an emulsifier (surfactant) is preferably adopted (forced emulsification). Polyurethane having a hydrophilic group such as a carboxy group is self-emulsified by dispersing it in water. Self-emulsifying water-based polyurethane is preferred because it can reduce the particle size.
[0033] The emulsion particle size of the water-based polyurethane is 30 nm or less. By using a water-based polyurethane with a small emulsion particle size, the turbidity of the adhesive composition is suppressed, and the haze of the adhesive layer formed by coating and drying the adhesive composition tends to be low. Therefore, an adhesive film with low haze and excellent transparency can be obtained.
[0034] From the viewpoint of reducing the haze of the easy-adhesion composition and the easy-adhesion layer (easy-adhesion film), the emulsion particle size of the water-based polyurethane is more preferably 25 nm or less, further preferably 20 nm or less, and may be 15 nm or less or 10 nm or less. The emulsion particle size of the water-based polyurethane is generally 1 nm or more, and may be 3 nm or more or 5 nm or more. The emulsion particle size of the water-based polyurethane is the median particle size (D50) based on the particle size measured by dynamic light scattering using an aqueous dispersion as a sample.
[0035] The water-based polyurethane may have a crosslinked structure. The introduction of a crosslinked structure into the polyurethane tends to improve the adhesion between the easy-adhesion film and the polarizer, etc. On the other hand, polyurethane having a crosslinked structure has a large emulsion particle size, so the haze of the easy-adhesion composition (solution) and the easy-adhesion layer tends to be high. In addition, when the polyurethane has a crosslinked structure, the viscosity of the solution is likely to increase or gel, and the solution stability of the easy-adhesion composition may be poor.
[0036] <Crosslinking agent> The adhesive composition may contain, as a binder resin component, a crosslinking agent having a functional group capable of reacting with the crosslinkable functional group of the polyurethane in addition to the aqueous polyurethane. By containing the crosslinking agent in the adhesive composition, a crosslinked structure is introduced into the polyurethane by heating during the formation of the adhesive layer. By using a polyurethane having no crosslinked structure as the aqueous polyurethane and containing a crosslinking agent in the adhesive composition, an adhesive layer having excellent adhesiveness can be formed while increasing the solution stability of the adhesive composition.
[0037] When the polyurethane has a carboxy group, a crosslinking agent containing an amino group, an oxazoline group, an epoxy group, a carbodiimide group, or the like is used. Among these, a crosslinking agent containing an oxazoline group is preferred. Since the oxazoline group has a low reactivity with the carboxy group at room temperature, an easily adhesive composition containing a water-based polyurethane and an oxazoline-based crosslinking agent is unlikely to cause an increase in viscosity or gelation over time, and has excellent solution stability.
[0038] The crosslinking agent may be a low molecular weight compound or a polymer. A water-soluble acrylic polymer is preferred as the crosslinking agent because it has high solubility in the aqueous composition and excellent compatibility with polyurethane. In particular, when an acrylic polymer having an oxazoline group is used as the crosslinking agent, the adhesion between the easy-adhesion film 1 and a film such as a polarizer tends to be improved.
[0039] The amount of the crosslinking agent in the easy-adhesion composition is preferably 1 to 30 parts by weight, more preferably 3 to 25 parts by weight, and even more preferably 5 to 20 parts by weight, based on 100 parts by weight of the solid content of the water-based polyurethane.
[0040] <Solvent> The adhesive composition containing the aqueous polyurethane as the binder resin is preferably an aqueous composition containing water as a solvent. The adhesive composition may contain, in addition to water, an organic solvent miscible with water as a solvent.
[0041] <Fine particles> The adhesive composition may contain fine particles in addition to the water-based polyurethane and crosslinking agent as the binder resin, and water as the solvent (and dispersion medium). When the adhesive composition contains fine particles, fine irregularities are formed on the surface of the adhesive layer 15, improving the slipperiness of the film. This contributes to reducing scratches on the adhesive film 1 during roll transport and suppressing blocking when the film is wound into a roll.
[0042] From the viewpoint of forming unevenness that contributes to improving the slipperiness, the particle diameter (average primary particle diameter) of the fine particles is preferably 10 nm or more, more preferably 15 nm or more, and even more preferably 20 nm or more. The average primary particle diameter of the fine particles is preferably smaller than the thickness of the easy-adhesion layer. When the particle diameter of the fine particles is smaller than the thickness of the easy-adhesion layer, the fine particles can be prevented from falling off from the easy-adhesion layer. The particle diameter of the fine particles is preferably 250 nm or less, and more preferably 200 nm or less. In addition, when the average primary particle diameter of the fine particles is smaller than the wavelength of visible light, the scattering of visible light at the interface between the binder resin and the fine particles can be prevented. From the viewpoint of improving transparency, the particle diameter of the fine particles is preferably 100 nm or less, more preferably 80 nm or less, even more preferably 60 nm or less, and particularly preferably 50 nm or less.
[0043] The fine particles may be either inorganic or organic. The fine particles are preferably inorganic because of their excellent dispersibility and uniformity of particle size. Examples of inorganic fine particles include inorganic oxides such as titania, alumina, and zirconia; calcium carbonate, talc, clay, calcined kaolin, calcined calcium silicate, hydrated calcium silicate, aluminum silicate, magnesium silicate, and calcium phosphate. Among these, inorganic oxides are preferred. Examples of organic fine particles include silicone resins, fluorine resins, and acrylic resins. In order to suppress light scattering caused by the fine particles, it is preferable that the refractive index difference between the binder resin (generally a refractive index of about 1.5) and the fine particles is small. The fine particles are preferably silica particles because of their small refractive index difference with the binder resin and excellent dispersibility.
[0044] For the aqueous adhesive composition, it is preferable to use fine particles having high water dispersibility. A water dispersion of fine particles may be blended into the composition. In order to increase the dispersibility of the fine particles, an alkaline component such as amine or ammonia may be added to make the adhesive composition weakly alkaline.
[0045] Colloidal silica is preferably used as the water-dispersible silica particles. As the colloidal silica, commercially available products such as the Quartron PL series manufactured by Fuso Chemical Industry Co., Ltd., the Snowtex series manufactured by Nissan Chemical Industries, Ltd., the AERODISP series and the AEROSIL series manufactured by Nippon Aerosil Co., Ltd., and the Seahorster KE series manufactured by Nippon Shokubai Co., Ltd. may be used.
[0046] From the viewpoint of increasing the slipperiness of the easy-adhesion film 1 by forming unevenness on the surface of the easy-adhesion layer 15, the content of the fine particles is preferably 3% by weight or more, more preferably 5% by weight or more, based on the total solid content of the easy-adhesion composition. In particular, when the thickness of the easy-adhesion layer 15 is small, it is preferable to increase the content of the fine particles to increase the amount of fine particles per unit area (number density) and thereby form unevenness uniformly within the surface of the easy-adhesion layer 15. The content of the fine particles in the easy-adhesion layer 15 is preferably 8% by weight or more, more preferably 10% by weight or more, and even more preferably 12% by weight or more. If the content of the fine particles in the easy-adhesion layer 15 is excessively large, it may lead to a decrease in optical properties due to an increase in light scattering at the interface between the binder resin and the fine particles. In addition, as the content of the fine particles increases, the relative content of the binder resin decreases, and therefore the adhesiveness of the easy-adhesion layer may decrease. Therefore, the content of the fine particles is preferably 50% by weight or less, more preferably 40% by weight or less, and even more preferably 30% by weight or less, based on the total solid content of the easy-adhesion composition.
[0047] <Other ingredients> The easy-adhesion composition may contain a resin component other than the water-based polyurethane as a binder resin, but from the viewpoint of ensuring the adhesion and transparency of the easy-adhesion film, the ratio of polyurethane resin (including a crosslinking agent capable of crosslinking with polyurethane) in the binder resin component is preferably 50% by weight or more, more preferably 70% by weight or more, more preferably 80% by weight or more, even more preferably 90% by weight or more, and may be 95% by weight or more, 98% by weight or more, 99% by weight or more, or 100% by weight.
[0048] The adhesive composition may contain an alkaline component such as ammonia or an amine for the purpose of improving the dispersibility of fine particles, etc. The adhesive composition may contain additives such as a catalyst such as a crosslinking accelerator, an antioxidant, a radical scavenger, an ultraviolet absorber, a leveling agent, an antiblocking agent, an antistatic agent, a dispersion stabilizer, an antifoaming agent, a thickener, a dispersant, a surfactant, and a lubricant.
[0049] <Preparation of Easy-Adhesion Composition> An easily adhesive composition is prepared by dissolving or dispersing an aqueous polyurethane as a binder resin, and, if necessary, a crosslinking agent, fine particles, an alkali component, and various other additives in water as a solvent (or an aqueous solvent mainly composed of water). From the viewpoints of solution stability and coatability, etc., the concentration of solids (non-volatile components) in the easily adhesive composition is preferably 1 to 30% by weight, more preferably 3 to 20% by weight, and even more preferably 5 to 15% by weight.
[0050] The solid content concentration of the aqueous polyurethane in the easy-adhesion composition is preferably 1 to 20% by weight, more preferably 2 to 15% by weight, further preferably 3 to 12% by weight, and may be 4 to 10% by weight. If the concentration of the aqueous polyurethane is too low, it is difficult to increase the thickness of the easy-adhesion layer, and the adhesion to the polarizer or the like may be insufficient. On the other hand, if the concentration of the aqueous polyurethane is too high, it may cause an increase in haze of the easy-adhesion film due to a decrease in the transparency of the solution (white turbidity) or a decrease in the stability of the solution.
[0051] From the viewpoint of coatability, the solution viscosity of the easy-adhesion composition at a temperature of 25° C. is preferably 1 to 100 cP, more preferably 2 to 50 cP, even more preferably 3 to 30 cP, and may be 4 to 20 cP or 5 to 15 cP. The easy-adhesion composition preferably has a viscosity change rate within ±100% when allowed to stand at room temperature for 24 hours after preparation, more preferably within ±50%, and even more preferably within ±30%.
[0052] The haze of the solution of the easy-adhesion composition measured using a measuring cell with an optical path length of 1 cm is preferably 40% or less. The smaller the emulsion particle size of the water-based polyurethane as the binder resin, the smaller the haze of the easy-adhesion composition and the smaller the haze of the easy-adhesion film tend to be. The haze of the easy-adhesion composition is more preferably 30% or less, more preferably 25% or less, and may be 20% or less or 15% or less. The haze of the easy-adhesion composition may be greater than 0, 1% or more, 3% or more, 5% or more, or 7% or more.
[0053] [Formation of easy-adhesion layer] The easy-adhesion composition is applied onto a film substrate 11, and the easy-adhesion composition on the film substrate is heated to remove the solvent, thereby forming an easy-adhesion film 1 having an easy-adhesion layer 15 on the film substrate 11.
[0054] Before applying the easy-adhesion composition onto the film substrate 11, the film substrate may be subjected to a surface treatment. By performing the surface treatment, the wetting tension of the film substrate can be adjusted, and the adhesion to the easy-adhesion layer 15 can be improved. Examples of the surface treatment include corona treatment, plasma treatment, ozone spraying, ultraviolet irradiation, flame treatment, and chemical treatment. Among these, corona treatment or plasma treatment is preferred.
[0055] Examples of the coating method of the easy-adhesion composition include a bar coating method, a roll coating method, a gravure coating method, a rod coating method, a slot orifice coating method, a curtain coating method, and a fountain coating method. The easy-adhesion composition after coating is heated to remove the solvent, thereby forming an easy-adhesion layer 15. The precursor of the binder resin may be reacted and cured by heating. For example, when the easy-adhesion composition contains a crosslinking agent, the crosslinking reaction can be promoted by heating.
[0056] The heating temperature during the formation of the easy-adhesion layer is, for example, about 50 to 200° C. From the viewpoint of promoting the curing reaction of the resin component in the easy-adhesion composition, the heating temperature is preferably 100° C. or higher, more preferably 120° C. or higher, even more preferably 130° C. or higher, and particularly preferably 135° C. or higher. When the easy-adhesion composition contains an alkali component such as amine or ammonia, from the viewpoint of efficiently volatilizing and removing the alkali component to reduce the amount of residual alkali, the heating temperature is preferably higher than the boiling point of the alkali component.
[0057] The easy-adhesion layer may be formed in the manufacturing process of the film substrate. The easy-adhesion layer may also be formed by utilizing heating during the formation of the film substrate. For example, when the film substrate is a stretched film, the easy-adhesion composition is applied to the surface of the film before stretching or the film after longitudinal stretching, and the solvent can be dried or the resin can be cured by utilizing heating during transverse stretching or simultaneous biaxial stretching by a tenter.
[0058] When the film substrate is stretched after applying the easy-adhesion composition, the stretching ratio is preferably 5 times or less, more preferably 4 times or less, even more preferably 3 times or less, and particularly preferably 2.5 times or less, from the viewpoint of suppressing defects such as cracking in the easy-adhesion layer. The lower limit of the stretching ratio is not particularly limited, but from the viewpoint of improving the film strength, the stretching ratio is preferably 1.3 times or more, more preferably 1.5 times or more. When the film substrate is an acrylic film, it is preferable to perform stretching at the above-mentioned stretching ratio in each of the machine direction (MD) and the transverse direction (TD) from the viewpoint of improving the film strength.
[0059] When the film substrate is biaxially stretched, the biaxial stretching may be sequential biaxial stretching or simultaneous biaxial stretching. In addition, oblique stretching may be performed. When sequential biaxial stretching is performed, as described above, the film is stretched in one direction (MD) by roll stretching, and then the easy-adhesion composition is applied onto the film, and the easy-adhesion composition may be heated during stretching by a tenter.
[0060] The thickness of the adhesive layer 15 can be adjusted by adjusting the solid content concentration and coating thickness of the adhesive composition. When the film substrate is stretched after coating the adhesive composition, the thickness of the adhesive layer 15 can also be adjusted by the stretching ratio.
[0061] The thickness of the easy-adhesion layer is not particularly limited, but is generally about 10 nm to 2 μm. From the viewpoint of improving adhesion to a polarizer or the like, the thickness of the easy-adhesion layer is preferably 110 nm or more, more preferably 130 nm or more, and may be 140 nm or more or 150 nm or more. From the viewpoint of suppressing unevenness in lamination when laminating with a polarizer or the like, and suppressing the occurrence of streaky unevenness when the polarizing plate is exposed to a humid environment, the thickness of the easy-adhesion layer is preferably 500 nm or less, more preferably 300 nm or less, even more preferably 280 nm or less, and may be 250 nm or less or 230 nm or less.
[0062] The total light transmittance of the easy-adhesion film is preferably 85% or more, more preferably 90% or more, and may be 91% or more or 92% or more. The haze of the easy-adhesion film is preferably 1.0% or less, more preferably 0.5% or less, and may be 0.3% or less or 0.2% or less. By using a highly transparent film such as an acrylic film as the film substrate 11 and using a water-based polyurethane with a small emulsion particle size as the binder resin of the easy-adhesion layer, an easy-adhesion film having an easy-adhesion layer with excellent adhesion to a polarizer and the like and high transparency can be obtained.
[0063] [Polarizing plate] As described above, the easy-adhesion film can be used as a polarizer protective film for a polarizing plate. The polarizing plate may have a polarizer protective film on only one side of the polarizer, or may have a polarizer protective film on both sides of the polarizer 5 as shown in FIG. 2. By bonding the above-mentioned easy-adhesion film as a polarizer protective film to one side of the polarizer, a polarizing plate having a transparent protective film only on one side of the polarizer is formed. A polarizing plate having a polarizer protective film on both sides of the polarizer may have the above-mentioned easy-adhesion film bonded to at least one side of the polarizer. The polarizing plate may have the above-mentioned easy-adhesion film bonded to both sides of the polarizer. The polarizer 5 and the easy-adhesion film 1 are bonded to each other via an adhesive layer 6.
[0064] <Polarizer> A polyvinyl alcohol (PVA)-based polarizer in which a dichroic substance such as iodine or a dichroic dye is adsorbed onto a polyvinyl alcohol-based film such as polyvinyl alcohol or partially formalized polyvinyl alcohol and aligned in one direction is used as the polarizer 5. For example, a PVA-based polarizer can be obtained by dyeing a polyvinyl alcohol-based film with iodine and stretching it.
[0065] <Adhesive> The adhesive layer 6 used for bonding the polarizer 5 and the easy-adhesion film 1 is not particularly limited in material as long as it is optically transparent, and examples of the material include epoxy resins, silicone resins, acrylic resins, polyurethane, polyamide, polyether, polyvinyl alcohol, etc. The thickness of the adhesive layer 6 is, for example, about 0.01 to 20 μm, and is appropriately set depending on the type of adherend, the adhesive material, etc. When a curing type adhesive that exhibits adhesiveness by a crosslinking reaction after application is used, the thickness of the adhesive layer 6 is preferably 0.01 to 5 μm, more preferably 0.03 to 3 μm.
[0066] The adhesive may be in any of various forms, such as a water-based adhesive, a solvent-based adhesive, a hot melt adhesive, an active energy ray curable adhesive, etc. Among these, a water-based adhesive or an active energy ray curable adhesive is preferred, since it allows the thickness of the adhesive layer to be reduced.
[0067] <Preparation of polarizing plate> A polarizing plate is manufactured by bonding the easy-adhesion film 1 to one surface of the polarizer 5 via an adhesive layer 6. The easy-adhesion film 1 may have the easy-adhesion layer-formed surface bonded to the polarizer 5 via an adhesive layer, or the easy-adhesion layer-non-formed surface bonded to the polarizer 5 via an adhesive layer. As shown in FIG. 2, by bonding the polarizer 5 to the easy-adhesion layer 15-formed surface of the easy-adhesion film 1 via an adhesive layer 6, a polarizing plate having high adhesion between the polarizer and the polarizer protective film (easy-adhesion film 1) and excellent mechanical strength and durability can be obtained. When the easy-adhesion layer-non-formed surface is bonded to the polarizer via an adhesive layer, the adhesion to other films, pressure-sensitive adhesive layers, glass substrates, etc. provided on the easy-adhesion film can be improved.
[0068] In bonding the polarizer 5 and the easy adhesion film 1, it is preferable to apply an adhesive composition to either one or both of the polarizer 5 and the easy adhesion film 1, and then bond the polarizer 5 and the easy adhesion film 1 together using a roll laminator or the like, and cure the adhesive. Examples of a method for applying the adhesive composition to the polarizer 5 and / or the easy adhesion film 1 include a roll method, a spray method, and a dipping method. Before applying the adhesive composition to the surface of the polarizer 5 and / or the easy adhesion film 1, a surface treatment such as a corona treatment, a plasma treatment, or a saponification treatment may be performed.
[0069] After the polarizer 5 and the easy-adhesion film 1 are attached to each other, the adhesive layer 6 is formed by curing the adhesive depending on the type of adhesive. When a water-based adhesive is used, the adhesive is cured by heating and drying. When an active energy ray-curable adhesive is used, the adhesive is cured by irradiating it with active energy rays such as electron beams or ultraviolet rays.
[0070] <Transparent protective film> A transparent protective film 2 may be attached to the other surface of the polarizer 5 via an adhesive layer 7. Any appropriate transparent film may be used as the transparent protective film 2. The transparent protective film 2 has a thickness of about 5 to 200 μm. From the viewpoints of mechanical strength, transparency, handleability, and the like, the transparent protective film 2 has a thickness of preferably 10 to 100 μm, more preferably 15 to 60 μm. The thicknesses of the easy-adhesion film 1 and the transparent protective film 2 may be the same or different.
[0071] Materials for forming the transparent protective film 2 include polyesters such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), etc.; cellulose-based polymers such as diacetyl cellulose and triacetyl cellulose; styrene-based polymers such as polystyrene and acrylonitrile-styrene copolymer; cyclic polyolefins such as polynorbornene; polycarbonate, etc.
[0072] The transparent protective film 2 may have an easy-adhesion layer (not shown) on the surface to be bonded to the polarizer 5. The transparent protective film 2 may have an easy-adhesion layer similar to the easy-adhesion layer 15 of the easy-adhesion film 1.
[0073] The adhesive layer 7 used for bonding the polarizer 5 and the transparent protective film 2 may be of various types, such as a water-based adhesive, a solvent-based adhesive, a hot melt adhesive, an active energy ray curable adhesive, etc. The same adhesive composition may be used for the adhesive layer 6 and the adhesive layer 7.
[0074] <Applications of polarizing plates> The polarizing plate can be used as a component of an image display device such as a liquid crystal display device or an organic EL display device. An image display device can be formed by laminating a polarizing plate to the surface of an image display cell such as a liquid crystal cell or an organic EL cell. A liquid crystal display device is formed by appropriately assembling a liquid crystal cell, a polarizing plate, and, if necessary, components such as an illumination system, and incorporating a driving circuit. In an organic EL display device, a circular polarizing plate that combines the polarizing plate of the present invention and a retardation film (typically a quarter-wave plate) is laminated to the surface of an organic EL cell, thereby reducing the re-emission of reflected light of external light by metal electrodes, etc., and improving visibility.
[0075] Since the above-mentioned easy-adhesion film has high transparency, a polarizing plate having the above-mentioned easy-adhesion film as a polarizer protective film has high single-piece transmittance and low haze, and can contribute to increasing the brightness and sharpness of an image display device. EXAMPLES
[0076] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following, the "%" regarding concentration is by weight unless otherwise specified.
[0077] [Example 1] <Preparation of Easy-Adhesion Composition> 20.0 parts by weight of water-based polyurethane with a solid content of 22% (DIC "Hydran AP-40F", emulsion particle size: 5 to 10 nm), 3.0 parts by weight of an oxazoline-containing polymer aqueous solution with a solid content of 25% (Nippon Shokubai "Epocross WS-700"), 5.0 parts by weight of a 20% aqueous dispersion of colloidal silica with an average primary particle size of 35 nm (Fuso Chemical Co., Ltd. "Quattron PL-3"), 3.0 parts by weight of 1% ammonia water, and 69.0 parts by weight of pure water were mixed to prepare an easily adhesive composition 1 (solid content concentration: 6.2%, ratio of polyurethane to total solid content: 71.5%, solid content concentration of polyurethane: 4.4%).
[0078] <Formation of an easily adhesive layer on an acrylic film> An easy-adhesion film was produced using a film production apparatus equipped with a melt extrusion film-forming apparatus, a gravure coater, a tenter-type simultaneous biaxial stretching apparatus, and a winding apparatus. As the acrylic resin, pellets of the same imidized MS resin (glass transition temperature: 120 ° C.) used in the production of "Transparent Protective Film 1A" described in the examples of JP 2017-26939 A were used. The acrylic resin was melt extruded from a T-die to produce a film with a thickness of 160 μm, and the above-mentioned easy-adhesion composition was applied to one side of the film with a wet thickness of about 6.5 μm using a gravure coater, and stretched twice in each of the longitudinal direction (MD) and transverse direction (TD) by a simultaneous biaxial stretching tenter in a heating furnace at a temperature of 140 ° C. to obtain an easy-adhesion film having an easy-adhesion layer with a thickness of 200 nm on one side of a 40 μm-thick acrylic film.
[0079] [Comparative Example 1] 6.5 parts by weight of water-based polyurethane with a solid content of 34% (Daiichi Kogyo Seiyaku's "Superflex 210R", emulsion particle size: 40 nm), 1.5 parts by weight of an oxazoline-containing polymer aqueous solution (Nippon Shokubai's "Epocross WS-700"), 2.5 parts by weight of a colloidal silica aqueous dispersion (Fuso Chemical's "Quatron PL-3"), 3.0 parts by weight of 1% ammonia water, and 86.5 parts by weight of pure water were mixed to prepare an easy-adhesion composition 2 (solid concentration: 3.1%, ratio of polyurethane to total solids: 71.6%, solid concentration of polyurethane: 2.2%). Using this easy-adhesion composition, an easy-adhesion film having an easy-adhesion layer with a thickness of 100 nm on an acrylic film was prepared in the same manner as in Example 1.
[0080] [Comparative Example 2] The amount of the aqueous polyurethane, the oxazoline-containing polymer aqueous solution, and the colloidal silica aqueous dispersion was doubled compared to Comparative Example 1, and the amount of pure water was changed to 76 parts by weight to prepare an easy-adhesion composition 3 (solid concentration: 6.2%, ratio of polyurethane to total solids: 71.6%, solid concentration of polyurethane: 4.4%). Using this easy-adhesion composition, an easy-adhesion film having an easy-adhesion layer having a thickness of 200 nm on an acrylic film was produced in the same manner as in Example 1.
[0081] [Comparative Examples 3 to 6] Except for changing the type and amount of water-based polyurethane and the amount of pure water, easy-adhesion compositions 4 to 7 (solid concentration: 6.2%, ratio of polyurethane to total solids: 71.6%) were prepared in the same manner as in Comparative Example 2, and easy-adhesion films having an easy-adhesion layer having a thickness of 200 nm on an acrylic film were produced.
[0082] The following water-based polyurethanes were used in Comparative Examples 3 to 6. The "Hydran RCP-A-220" used in Comparative Example 6 (easy-adhesion composition 7) was a crosslinked polyurethane, and the polyurethanes used in the other examples did not have a crosslinked structure. Comparative Example 3 (easy-adhesion composition 4): "Takelac W-6010" manufactured by Mitsui Chemicals, emulsion particle size: 60 nm Comparative Example 4 (easy-adhesion composition 5): "Takelac W-605" manufactured by Mitsui Chemicals, emulsion particle size: 80 nm Comparative Example 5 (easy-adhesion composition 6): "Takelac W-6061" manufactured by Mitsui Chemicals, emulsion particle size: 100 nm Comparative Example 6 (Easy-Adhesion Composition 7): "HYDRAN RCP-A-220" manufactured by DIC, emulsion particle size: 100 nm)
[0083] [evaluation] <Evaluation of easy-adhesion composition (solution)> (viscosity) Immediately after preparation, the solution viscosities of the adhesive compositions 1 to 7 used in the production of the adhesive films of the Examples and Comparative Examples were measured using a B-type viscometer at a temperature of 25° C. Thereafter, the compositions were allowed to stand at room temperature (25° C.) for 24 hours, and the viscosities were measured again to evaluate the change in viscosity.
[0084] (Solution Haze) The easily adhesive composition immediately after preparation was filled into a measurement cell with an optical path length of 1 cm, and the haze of the solution was measured using a haze meter ("NDH-8000" manufactured by Nippon Denshoku Industries Co., Ltd.).
[0085] <Evaluation of easy-to-adhere films> (Haze and total light transmittance) The haze and total light transmittance of the easy-adhesive film were measured using a haze meter ("NDH-8000" manufactured by Nippon Denshoku Industries Co., Ltd.).
[0086] (Adhesive strength of easy-adhesive layer) A polarizing plate was produced by laminating an easy-adhesion film to one side of a 18 μm-thick polyvinyl alcohol polarizer and a biaxially stretched cyclic polyolefin film (ZEON Corporation's "ZEONOR Film ZF-14") to the other side. A photoradical curing adhesive (containing 40 parts by weight of N-hydroxyethyl acrylamide and 60 parts by weight of acryloyl morpholine as curing components) was applied to a thickness of about 1 μm on the easy-adhesion layer-forming surface of the easy-adhesion film and on the surface of the ZEONOR film, and the polarizer was laminated using a roll laminator. After that, the polarizer was laminated using an integrated light intensity of 1000 mJ / cm. 2 The adhesive was cured by exposure to ultraviolet light.
[0087] The polarizing plate was cut into a size of 200 mm parallel to the stretching direction of the polarizer (absorption axis direction) and 15 mm perpendicular to the stretching direction (transmission axis direction), and a cut was made between the easy-adhesion film and the polarizer with a cutter knife, and then the surface of the polarizing plate on the Zeonor film side was attached to a glass plate. A peel test was performed using a tensile compression tester (Minebea's "TG-1kN") at a peel angle of 90° and a peel speed of 1000 mm / min to measure the adhesive strength between the polarizer and the easy-adhesion film. Adhesive strengths of 2.0 N / 20 mm or more were rated as ◯, and those less than 2.0 N / 20 mm were rated as ×.
[0088] [Evaluation Results] The evaluation results of the easily adhesive compositions and easily adhesive films of the examples and comparative examples are shown in Table 1.
[0089] [Table 1]
[0090] Example 1 (easy-adhesion composition 1), which used a water-based polyurethane with a small emulsion particle size, had low solution haze, low viscosity, and no change in viscosity over time, and was excellent in solution stability. The easy-adhesion film of Example 1 had high transparency and excellent adhesion to the polarizer.
[0091] In Comparative Example 2 (easy-adhesion composition 3), which used a water-based polyurethane having an emulsion particle size of 40 nm or more, the solution stability was good, but the haze of the solution was high, and the easy-adhesion film produced using this easy-adhesion composition had a high haze and poor transparency compared to Example 1. In Comparative Example 1 (easy-adhesion composition 2), in which the solid content concentration of the solution was halved, the haze of the solution was smaller than in Comparative Example 2, and the transparency of the easy-adhesion film was improved, but the transparency was poorer than in Example 1. In addition, in Comparative Example 1, the thickness of the easy-adhesion layer was small, so the adhesion of the easy-adhesion film to the polarizer was insufficient.
[0092] In Comparative Examples 3 to 6 (easy-adhesion compositions 4 to 7), which used water-based polyurethane with a larger emulsion particle size than in Comparative Example 2, the haze of the easy-adhesion composition and the easy-adhesion film tended to increase with an increase in the emulsion particle size. Comparative Example 6 (easy-adhesion composition 7), which used a crosslinked water-based polyurethane, had poor solution stability and insufficient adhesion between the easy-adhesion film and the polarizer.
[0093] The above results show that by using a solution of an aqueous polyurethane with a small emulsion particle size, it is possible to obtain an easily adhesive film that has low haze and excellent transparency, and also has high adhesive strength to an adherend such as a polarizer. [Explanation of symbols]
[0094] 1. Easy-adhesive film 11 Film substrate 15 Easy adhesive layer 2. Transparent film 5 Polarizer 6,7 Adhesive layer 100 Polarizing Plate
Claims
1. A method for producing an easy-adhesion film having an easy-adhesion layer on a surface of a transparent film substrate, comprising: A step of applying an easy-adhesion composition onto a transparent film substrate; and A step of heating the adhesive composition to remove the solvent. Including, The easy-adhesion composition is an aqueous solution containing a water-based polyurethane, The emulsion particle size of the water-based polyurethane is 30 nm or less. A method for producing an easily adhesive film.
2. The water-based polyurethane is a polyurethane having no crosslinked structure, The easy-adhesion composition further contains a crosslinking agent capable of crosslinking with the water-based polyurethane. A method for producing the easily adhesive film according to claim 1.
3. The method for producing an easily adhesive film according to claim 1 or 2, wherein in the step of removing the solvent, the transparent film substrate to which the easily adhesive composition is applied is stretched in at least one direction while being heated.
4. The method for producing an easily adhesive film according to claim 1 or 2, wherein the easily adhesive composition further contains fine particles.
5. The method for producing an easily adhesive film according to claim 1 or 2, wherein the easily adhesive layer has a thickness of 110 nm or more.
6. The easily adhesive film according to claim 1 or 2, wherein the transparent film substrate is an acrylic film.
Citation Information
Patent Citations
Optical multilayer film and image display device
JP2008209877A
Optical article and method for manufacturing the same
JP2010204456A
Coating material composition for forming primer layer film, and plastic lens
JP2011099074A
Cyclic olefinic film, optical film, conductive film, base film for printed electronics, barrier film, touch panel, polarizing plate and display device
JP2015160434A
Easy-adhesion film, polarizing plate, polarizing plate with binder, and image display device
JP2023061190A